Simplified Selvester QRS Score as an Infarct Size Parameter in STEMI Patients Undergoing Pharmacoinvasive or Primary Percutaneous Coronary Intervention - Arif Eka Prasetya; Anggoro Budi Hartopo; Nahar Taufiq; Hendry Purnasidha Bagaswoto; Budi Yuli Setianto (Jurnal Kardiologi Indonesia, 2025)
In “Simplified Selvester QRS Score as an Infarct Size Parameter in STEMI Patients Undergoing Pharmacoinvasive or Primary Percutaneous Coronary Intervention” (Indonesian Journal of Cardiology, 43(4), 150-8. https://doi.org/10.30701/ijc.1186), there is an error noted. An error has been found in the PDF version of this article. The DOI printed in the PDF is incorrect. The correct DOI is https://doi.org/10.30701/ijc.1186. The error occurs only in the PDF; the DOI listed in the article metadata is already correct. The publisher apologizes for any inconvenience caused by this error.